2004
DOI: 10.1159/000077702
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Change in a Clinical Sample of Problem Drinkers: Relation to Alcohol Use, Self-Efficacy, and Treatment Outcome

Abstract: According to the transtheoretical model of behaviour change, individuals addicted to psychotropic drugs typically cycle through a sequence of five discrete stages (precontemplation, contemplation, preparation, action, and maintenance) before achieving sustained long-term abstinence and moderation, respectively. A number of English-language questionnaires have been developed to assess client motivation in accordance with the stages of change approach. The present study aimed to expand the research on the transt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 24 publications
6
50
1
2
Order By: Relevance
“…This fi nding is consistent with the majority of studies that report no gender differences on measures of readiness to change (Blume et al, 2006;Demmel et al, 2004;Rumpf et al, 1999;Shealy et al, 2007). In a sample of heavy drinkers, Satre and colleagues (2011) also found that gender did not predict alcohol problem recognition.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This fi nding is consistent with the majority of studies that report no gender differences on measures of readiness to change (Blume et al, 2006;Demmel et al, 2004;Rumpf et al, 1999;Shealy et al, 2007). In a sample of heavy drinkers, Satre and colleagues (2011) also found that gender did not predict alcohol problem recognition.…”
Section: Discussionsupporting
confidence: 78%
“…There is considerable cross-sectional evidence that problem recognition and taking action are correlated with drinking severity and drinking outcomes (Bertholet et al, 2009;Demmel et al, 2004). However, although some of these studies reported that high scores on the ambivalence/ problem recognition factor was a signifi cant correlate of abstinence, number of drinks, number of drinks per drinking day, number of heavy drinking days, and number of negative drinking consequences, most studies were not able to model levels of alcohol severity on dimensional measures of motivation to change and subsequent drinking behavior over time .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the value of screening all patients who present with injuries for possible substance-related problems as these injuries may offer a window of opportunity for intervening with patients when they are more likely to recognise the negative consequences of continued substance use. In addition and similar to other studies [22,36,55], we found that greater problem severity (as reflected in more symptoms of depression and more complex substance use problems, such as methamphetamine use) was positively associated with more recognition that change was needed. Even though our findings suggest that individuals with greater substance use problem severity may not respond as well to BIs interventions as those with less severe problems, we are not suggesting that these individuals are not provided with a BI.…”
Section: Discussionsupporting
confidence: 88%
“…Stages of Change Readiness and Treatment Eagerness Scale. A German-language version of the SOCRATES (SOCRATES-G [33], [34]) was used to assess client motivation in accordance with the transtheoretical model. The SOCRATES-G comprises 19 items reflecting readiness to change drinking behavior.…”
Section: Methodsmentioning
confidence: 99%